PENGARUH MEDIA PADA PROSES PENGANGKUTAN TERHADAP PERTUMBUHAN BIBIT RUMPUT LAUT Kappaphycus alvarezii - Indri Yohanes; Sunadji Sunadji; Marcelien Dj Ratoe Oedjoe (Nusa Cendana University, 2020)
Seaweed is a macroalga that is found in all the world’scoastal acosystems, with avital role in maintaining biodiversity in coastal environments. Kelpis a low-level plant that cannot be differentiated between the root, the stem, and leaf, all the parts being called thullus. Seawed also has many uses as a producer of agar, alginate, and doub. Thr study is conducted for 60 days in the Agricultural waters of the village Batubao, kec. Kupang Barat, Kab Kupang, and by the Lab of marine collage and chemical loboratory of the agriculture department, Nusa Cendana University. The purpose of research is to know the effects of a different media on the growth of the seaweed seed Kappahycus alvarezii, as well as to the growing diversity and proksimat of Kappaphycus alvarezii. Experimental methods with 3 treatments and 3 deuteronomy. Data obtained are treated using a veriatal anova analysis. The study uses a different medium of treatment A (sawdust), treatment B (Straw), treatment C (ice cube). Reseach shows that the media used has definite on the growth and trexity of the proccylic content. This is seen is treatment A (Sawdust) giving an average lowest growth of 195.69 g, and B (straw) and C (ice cube) treatment 0f 330,54 g. the heig percentage of the doubt is antributted to C treatment 37,5%. Wheraes B treatment at 32,5%, whereas treatment at 30,2% and 65% of proccympichs from dry materials at 61,51% were given preasentations of raw protein contant, raw fats, carbohidratates,nitrogen free mater 34,285%, 4,636%, 1,4469%, 28,180%, 28,180%. Keywords: Seaweed, Growth, carrageenan, Kappaphycus alvarezii